BINGKAI BERITA KUNJUNGAN KERJA KOMISI A DPRD JATIM KE BELANDA TERKAIT HARI JADI JATIM DALAM LEMBAGA PENYIARAN PUBLIK (LPP) TVRI JATIM DAN LEMBAGA PENYIARAN SWASTA (LPS) LOKAL JTV SURABAYA - Melissa, Melissa; Hadi, Ido Prijana; Krisdinanto, Nanang (Institute of Research and Community Outreach - Petra Christian University, 2009)
Media construct and make sense of the reality it serves to its audiences. Reality-construction and sense-making are influenced by internal (reporters, media organization) and external factors (sources, advertisers, others). Thus, news is a product of constructed reality. News is not something that is already out-there for the media to present to its audiences. Media chooses, selects, put emphasis on some details and facts, while (purposedly) overlooks others. The selection and emphasise are called framing. Framing enables the complex, disorganized realities, to be changed into organized, simple, and sensible realities. In this research, the news the A-Committee’s excursion to Netherlands in relation to East Java’s centenary in Public Service Broadcasting TVRI Jatim and Commercial (Private) Broadcast JTV are explored. Since the research intends to see how the media presents, exnominates, and puts emphasis on facts and details to make sense of the reality, this research uses Zhongdang Pan and Gerald M. Kosicki’s framing analysis method. Hence, it was found, TVRI frames reality from the government’s point of view, while JTV frames the reality from the watchdog role’s point of view. The differences lays in historical, legal, and influences on media content. Thus, it was found that either public or commercial broadcasts television produce news according to their bias and interests that are seen through their newsframes.